2008
DOI: 10.1074/jbc.m709405200
|View full text |Cite
|
Sign up to set email alerts
|

NfuA, a New Factor Required for Maturing Fe/S Proteins in Escherichia coli under Oxidative Stress and Iron Starvation Conditions

Abstract: Iron/sulfur (Fe/S) proteins are central to the functioning of cells in both prokaryotes and eukaryotes. Here, we show that the yhgI gene, which we renamed nfuA, encodes a two-domain protein that is required for Fe/S biogenesis in Escherichia coli. The N-terminal domain resembles the so-called Fe/S A-type scaffold but, curiously, has lost the functionally important Cys residues. The C-terminal domain shares sequence identity with Nfu proteins. Mössbauer and UV-visible spectroscopic analyses revealed that, upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
151
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 44 publications
13
151
5
Order By: Relevance
“…Such variations in the [Fe-S] protein maturation process in different organisms are probably linked to physiological conditions, most significantly, intracellular redox conditions. Results similar to those reported here using A. vinelandii have also been found for the NfuA protein from E. coli (45).…”
Section: Discussionsupporting
confidence: 79%
“…Such variations in the [Fe-S] protein maturation process in different organisms are probably linked to physiological conditions, most significantly, intracellular redox conditions. Results similar to those reported here using A. vinelandii have also been found for the NfuA protein from E. coli (45).…”
Section: Discussionsupporting
confidence: 79%
“…A commonly used approach when characterizing FeS cluster scaffold and carrier proteins is to assess their capacity to transfer FeS clusters, intact, to partner carriers or model FeS client apoproteins (8,16,17). Indeed, the in vitro transfer of an FeS cluster from A. vinelandii IscU scaffold protein to the monothiol glutaredoxin A. vinelandii Grx5 and the transfer of an FeS cluster from A. vinelandii Grx-nif (among others) to the A. vinelandii Nif IscA carrier protein have recently been reported (13,36).…”
Section: Discussionmentioning
confidence: 99%
“…One potential clue as to in vivo GrxD function in E. coli comes from protein-protein interaction data (14). Sequential peptide affinity (SPA) purification of native levels of GrxD-SPA and BolA-SPA affinity-tagged proteins revealed that although GrxD co-purified with only small amounts of BolA, the affinity purification of BolA resulted in the co-purification of GrxD and small quantities of several other proteins including MiaB (14,15) and the recently characterized NfuA (8,16). 3 These data therefore implicated GrxD (and/or BolA) and NfuA in in vivo binding of, and potential FeS cluster transfer to, a client FeS apoprotein in MiaB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include the following: CyaY, an iron-binding protein believed to be involved in iron trafficking and iron delivery (5-7); YggX, an Fe 2ϩ -binding protein that protects the cell from oxidative stress (8,9); ErpA, an alternate A-type [Fe-S] cluster scaffolding protein (10); NfuA, a proposed intermediate [Fe-S] delivery protein (11)(12)(13); YtfE, a protein proposed to be involved in [Fe-S] cluster repair (14,15); and CsdA-CsdE, an alternative cysteine desulferase (16).…”
Section: Nifusvcyse1) Involved In the Biosynthesis Of [Fe-s] Clustersmentioning
confidence: 99%